DEVELOPMENT AND VALIDATION OF METHODS FOR DETERMINING THE AMOUNT OF FREE AND RELATED SIMPLE SUGARS IN THE FRUIT OF SEA BUCKTHORN - O. V. Trineeva; M. A. Kazmina; A. I. Slivkin (Разработка и регистрация лекарственных средств)
Developed and validated method of determining the amount of free and bound sugars picric method in the fruit of sea buckthorn. Validation assessment methodology characteristics: specificity, linearity, limit of detection, intra- and inter-laboratory reproducibility and repeatability demonstrated its compliance with the basic eligibility criteria. A determination of the amount of simple sugars and polysaccharides in the fruit of sea buckthorn of pharmacopoeial methods (ortsine and anthrone methods). It established the content of free and bound sugars in the fruit. The stability of the complex polysaccharide in the fruit of sea buckthorn on drying.